Effect of External Teat Sealant on the Prevention of Intramammary Infection for Milking Cows: A Randomized Cross-Over Design Study - Yasunori Shinozuka; Takuya Kanda; Keiichi Hisaeda; Akira Goto; Yoichi Inoue; Naoki Yamamoto (Microorganisms)
This study clarified the effectiveness of external teat sealant (ETS) in preventing intramammary infections during lactation, using a cross-over study of two experiments (3 cows × 2 periods each) on a dairy farm. In Experiment 1, the control (Group A) received pre-dip and post-dip treatments, while the experimental group (Group B) received ETS application instead of post-dip treatment. In Experiment 2, Group C was treated the same as Group B, and Group D received ETS treatment only. After the intervention, teat ends were tested using ATP swabs, and milk collections from the first and last foremilk (Samples 1 and 2, respectively) were conducted over 4 days (8 times in total). In Experiment 1, the ETS application group exhibited lower ATP (p < 0.01) and bacterial counts (BC1, p = 0.02) compared to the control. Conversely, no differences in variables were observed in Experiment 2. The isolation rate of Staphylococcus spp. (>500 colony forming units) from Sample 2 in Groups C and D was significantly higher than that in groups A and B (p < 0.01). Replacing post-milking teat disinfection with ETS does not decrease viable bacterial counts and actually increases the proportion of Staphylococcus spp. ETS application is thus not an effective substitute for teat orifice disinfection.